2007
DOI: 10.1021/jp073516e
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Thermodynamic Analysis of Sublimation Rates Using an Atomic Force Microscope

Abstract: Atomic force microscopy (AFM) has been successfully used to study the activation energy for evaporation of pentaerythritol tetranitrate (PETN) nanoislands formed by spin coating. These islands are annealed isothermally in the temperature range of 30-70 degrees C for a given time and are scanned with AFM in contact mode at room temperature. The volume of these islands does not change significantly up to about 35-40 degrees C indicating that sublimation is not significant below 40 degrees C. Above 40 degrees C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 19 publications
4
35
0
Order By: Relevance
“…From Table I it is found that the activation energy first decreases with introduction of Zn ions and attains a minimum value of 29.7 Kcal/mol for 1,000 ppm Zn doping from a value of 34.9 Kcal/mol for pure PETN with an error of 78 Kcal/mol. This value of activation energy for pure PETN is similar to literature values (Burnham et al 2009;Pitchimani et al 2007a). The decrease of activation energy due to doping of Zn ion is consistent with the result found by Pitchimani et al (2007c) for PETN crystal.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…From Table I it is found that the activation energy first decreases with introduction of Zn ions and attains a minimum value of 29.7 Kcal/mol for 1,000 ppm Zn doping from a value of 34.9 Kcal/mol for pure PETN with an error of 78 Kcal/mol. This value of activation energy for pure PETN is similar to literature values (Burnham et al 2009;Pitchimani et al 2007a). The decrease of activation energy due to doping of Zn ion is consistent with the result found by Pitchimani et al (2007c) for PETN crystal.…”
Section: Resultssupporting
confidence: 91%
“…Tung et al (1999) used the AFM to study the structure and growth kinetics of TNT and PETN films on various substrates and determined the sublimation rates of TNT film on silica by tapping mode AFM and ellipsometry. Pitchimani et al (2007a) prepared PETN thin films by spin coating and studied quantitatively the sublimation rates, and activation energy, at temperature ranging from 20-651C by AFM. They showed that the activation energy found at lower temperature is well matched with the results found for single crystals by thermogravimetric analysis (TGA).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is generally valid for thick cantilevers such as those used in our study. It should be mentioned that explosives generally form islands during the adsorption process as observed with atomic force microscopy (Pinnaduwage et al ., 2004, Pitchimani et al ., 2007. After the TNT loading was completed, a 10-V electrical pulse was sent to heat the cantilever.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, atomic force microscopy (AFM) and thermogravimetric analysis (TGA) have been used to study the molecular mobility and evaporation rate of PETN crystals [11,12]. In situ AFM was used to monitor morphology changes in the (11 0) surface of PETN.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the decay of islands was measured as a function of time for temperatures ranging from 30-65 1C. These studies found that the change in the volume and height of the islands was significant for temperatures above 40 C and obtained an activation energy for evaporation of 33.50 kcal/mol [11]. On the other hand, the rate of mass loss was measured using TGA by heating PETN crystals at temperatures from 110-135 1C and yielded an activation energy of 32.50 kcal/mol [12].…”
Section: Introductionmentioning
confidence: 99%